Varicella-associated immune thrombocytopenic purpura in a child with bleeding manifestations with review of literature - Kumar, Mukesh (Indian Journal of Child Health, 2017)
Chickenpox is a benign and self-limiting viral exanthematous infection, but sometimes it may be associated with complications. Mild thrombocytopenia occurs in 1-2% of children with varicella, but severe immune-mediated thrombocytopenia associated with bleeding is a rare complication. Various other mechanisms for thrombocytopenia have been implicated-decreased bone marrow production of platelets, disseminated intravascular coagulation, virally-induced platelet aggregation followed by phagocytosis or lysis, direct viral invasion of platelet precursors and viral-derived neuraminidase causing enzymatic desialylation of platelets followed by removal of abnormal platelets by reticuloendothelial system. We report a case of severe thrombocytopenia, possibly immune-mediated with bleeding in the form of petechiae and epistaxis in a child recovering from chickenpox, who is successfully treated with steroids. This may at least in part guide clinicians to recognize this rare but potentially dangerous complication of chickenpox.